Unpacking Teachers' Feedback on Students' Writing: A Content Analysis of Writing Exemplars - Tukan, Antonius Ikrar Asmarajati Laga; Mukarto, Fransiscus Xaverius (Universitas Pahlawan Tuanku Tambusai, 2024)
Feedback is crucial for facilitating student learning and growth. Recognizing the significance of effective feedback provision, this study aimed to elucidate the types and aspects of feedback from teachers crucial for enhancing student writing proficiency. The study centers on analyzing teachers' written feedback provided on student writing exemplars sourced from the New Zealand Curriculum. Employing content analysis methodology, the researchers investigated the feedback types employed by teachers to improve student writing skills. The findings revealed a varied distribution of feedback types he results of the study on writing exemplars at different levels indicate that feedback is given both directly and indirectly, with a focus on form in the lower levels of writing and a shift towards a focus on content in the higher levels. The feedback is fairly balanced between direct and indirect, with a higher percentage of indirect feedback. In the lower levels, form-focused feedback dominates, while in the higher levels, content-focused feedback becomes more prominent. This suggests a progression in the emphasis on content as writing skills develop. It suggests that indirect feedback is particularly conducive to enhancing writing proficiency among advanced students, empowering them to independently rectify errors. By uncovering the subtle interaction between different feedback approaches and the proficiency levels of student writers, our study provides meaningful perspectives for teachers aiming to enhance feedback strategies.